2021
DOI: 10.21203/rs.3.rs-995940/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing In Vitro Multiplication of some Olive Cultivars Using Silver, Selenium And Chitosan Nanoparticles

Abstract: Olive trees are commercially propagated by cuttings or grafting on clonal or seedling rootstocks; recently, olive micropropagation has emerged as a powerful technique for mass production of true to type and pathogen free plants. The current study was carried out to evaluate the effect of silver, chitosan and selenium nanoparticles as microbial decontamination agents, as well as evaluate its possible effects on in vitro shoot growth and multiplication of three olive cultivars namely Koroneiki, Picual and Manzan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…It is very important to determine the most effective and the lowest disinfection dose for the surface sterilization of an explant [37]. Although several chemicals like hydrogen peroxide, mercury, silver nitrate, and antibiotics can be used for seed surface sterilization, commercial sodium hypochlorite (bleach) is commonly used for the purpose [38,39]; yet the NaOCl is the most preferred disinfectant used World over [40, 41,], this study showed no signi cant distinction in seed germination behavior of the two rice cultivars. and showed that NaOCl-based seed disinfection was rice seed friendly [42].…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to determine the most effective and the lowest disinfection dose for the surface sterilization of an explant [37]. Although several chemicals like hydrogen peroxide, mercury, silver nitrate, and antibiotics can be used for seed surface sterilization, commercial sodium hypochlorite (bleach) is commonly used for the purpose [38,39]; yet the NaOCl is the most preferred disinfectant used World over [40, 41,], this study showed no signi cant distinction in seed germination behavior of the two rice cultivars. and showed that NaOCl-based seed disinfection was rice seed friendly [42].…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Darwesh and colleagues in 2023, an investigation was undertaken to assess the impact of silver, chitosan, and selenium nanoparticles on the in vitro growth of plantlets from three distinct olive cultivars: Koroneiki, Picual, and Manzanillo. The introduction of nanoparticles into the growth medium yielded noteworthy effects on the proliferation and growth rate of in vitro olive plants [44]. Therefore, we may suggest that phyto-mediated SeNPs elicited the rooting development of C. tuberculata by interfering with endogenous auxin…”
Section: Selenium Nanoparticles Mediated Micropropagation and Growth ...mentioning
confidence: 94%
“…Selenium nanoparticle solutions at two different concentrations (2.5 and 5 mg l −1 ) were obtained through personal communication with Professor Osama Darwish. Both solutions have been previously prepared by Darwish et al [10]. Stock solutions of both 100 mM sodium selenite and 50 mM ascorbic acid were prepared using sterile deionized water.…”
Section: Preparation Of Selenium Nanoparticlesmentioning
confidence: 99%